The Existence and Meaning of Betawi Dance in Setu Babakan: A Social Semiotic Study - Ghaisani, Afrina; Siregar, Iskandarsyah; Susanto, Arju (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
This research analyzes the existence, community participation, and cultural meaning of Betawi Dance in Setu Babakan. The aim is to find out the current conditions, the frequency of people's interest in Betawi dance at Setu Babakan, and the meanings of the Yellow Sirih Dance, Uncul Dance and Betawi Mask Dance. The theory used in this research is the theory of Social Semiotics, accompanied by its supporting theory, namely the theory of Sociology. The method used in this research is mixed methods, namely combining two qualitative and quantitative methods to obtain a more complete and in-depth view and answer to the problem being studied. This research also uses data collection techniques through observation and questionnaires. From the results of this research, Betawi dance in Setu Babakan is still ongoing, but its frequency fluctuates due to several factors. The government and Setu Babakan management must work together to arouse public interest, one way is to attract people to learn the meaning of Betawi dance which has values related to people's lives.